Foundation Funding and the Boundaries of Journalism. (26th October 2019) - Scott, Martin; Bunce, Mel; Wright, Kate
ABSTRACT: Private foundations are an important source of funding for many news outlets. It has even been suggested that they may offer a partial solution to journalism's economic crisis. Yet we do not know how foundation funding shapes journalistic practice. In this article, we show that foundation funding has a significant effect on the "boundaries of journalism". That is, the ways in which journalists understand, value and practice their journalism. This argument is based on 74 interviews with the most active foundations funding international non-profit news and the journalists they support. In general, we found that these foundations did not try to directly influence the content of the journalism they funded. However, their involvement did make a difference. It created requirements and incentives for journalists to do new, non-editorial tasks, as well as longer-form, off-agenda, "impactful" news coverage in specific thematic areas. As a result, foundations are ultimately changing the role and contribution of journalism in society. We argue that these changes are the result of various forms of "boundary work", or performative struggles over the nature of journalism. This contrasts with most previous literature, which has focused on the effects of foundation funding on journalistic autonomy.